FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018 - 2020) - Julistira, Adhe; Tohari, Amin; solikah, Mar'atus (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
This study aims to determine the effect of audit fees, audit tenure, hood rotation on audit quality both partially and simultaneously in Manufacturing Sector Companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. This study suggests that whether later audit quality can be measured by determined variables where the KAP rotation variable has not been widely taken by previous researchers. The sample used in this study were 58 Manufacturing Sector Companies listed on the Indonesia Stock Exchange. Then the data was analyzed using the SPSS for windows version 20 program using the logistic regression method. The results of this study are (1) The results of logistic regression indicate that the audit fee variable has no effect on audit quality. (2) The results of the logistic regression test in this study indicate that audit tenure has no effect on audit quality. (3) The results of the logistic regression test show that KAP rotation has no effect on audit quality. Keywords: audit fee, audite tenure, hood rotation, and quality audit